Literature Review: Analysis of Articles on the Application of Role-Playing Method in Improving Speaking Skills of Elementary School Students - Maulana, Adam; Pebriana, Putri Hana; Hidayanti, Eka Nur; Arini, Dian Widityastuti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Speaking is a vital linguistic skill as it is used in everyday life. However, research indicates that students' speaking abilities remain low, primarily due to limited resources to practice speaking in class and a lack of confidence. One solution to enhance this skill is by implementing the role-playing method in the learning process. This study aims to evaluate how well the role-playing approach can improve elementary school students' speaking skills. The study utilizes a literature review by analyzing eleven relevant articles published in the last five years, sourced from Google Scholar. The findings reveal that the role-playing method is an engaging and innovative teaching approach that effectively helps students develop their speaking abilities, particularly at the elementary level